Preparation method and application of in-situ cross-linked graphene oxide-hybrid silicon reverse osmosis membrane
The in-situ crosslinked graphene oxide-hybrid silicon reverse osmosis membrane preparation method solves the problems of easy swelling of graphene oxide membrane and insufficient preparation methods, and improves the stability and separation performance of the membrane, making it suitable for reverse osmosis desalination.
Patent Information
- Application Number
- CN202510852199.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-24
- Publication Date
- 2025-11-18
AI Technical Summary
Existing graphene oxide membranes are prone to swelling in water, which leads to a decrease in separation performance. Furthermore, existing preparation methods suffer from problems such as uneven membrane thickness and high mass transfer resistance, which affect their application effectiveness.
An in-situ crosslinked graphene oxide-hybrid silicon reverse osmosis membrane was prepared by initially crosslinking graphene oxide nanosheets with a hybrid silicon precursor and then acid-catalyzed in-situ crosslinking to form a composite sol, which was then coated onto a ceramic support to form a membrane. The hybrid silicon network was used to support the GO nanosheet layer and improve its hydrophilicity.
It achieves improved membrane structural stability and separation performance, with excellent water permeability and salt rejection rate, making it suitable for reverse osmosis desalination and exhibiting excellent structural stability and high-efficiency separation performance.
Smart Images

Figure CN120960988A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of composite membranes, and particularly relates to a preparation method of an in-situ cross-linked graphene oxide-hybrid silicon reverse osmosis membrane and application thereof. BACKGROUND
[0002] In recent years, two-dimensional carbon material graphene has been widely applied in separation membranes due to its outstanding physical and chemical properties. So far, graphene-based separation membranes can be mainly divided into three categories: the first category is a porous membrane, which is constructed by laser under harsh conditions to have different size pore diameters; the second category is a mixed matrix membrane, which mainly dopes graphene material into an organic matrix to fully utilize the excellent physical and chemical properties of graphene material, so as to improve separation performance; and the third category is mainly to utilize the structural characteristics of graphene material to stack layer by layer into a membrane for separation of ions, liquids and gases.
[0003] However, the existing graphene oxide membrane will swell in water, which will cause a substantial decline in material separation performance, and seriously restricts the membrane preparation process and actual application. Therefore, it is extremely difficult to precisely control the interlayer spacing of GO nanosheets, to overcome the swelling phenomenon under humidity conditions, to ensure the stability of the physical and chemical properties at the interface, and finally to realize the precise control of the interlayer spacing at the sub-nanometer size.
[0004] At present, hybrid silicon materials with organic bridging structures have attracted much attention of researchers due to their high specific surface area, excellent hydrothermal stability and chemical stability. Common methods for preparing bridged organic silicon separation membranes include spin coating and tape casting, but there are still some deficiencies. For example, the film prepared by the spin coating method is not uniform in thickness and defects are prone to occur; the film prepared by the tape casting method is generally thick, has large mass transfer resistance, and has low membrane flux. SUMMARY
[0005] The purpose of this section is to summarize some aspects of the embodiments of the application and briefly introduce some preferred embodiments.
[0006] In view of the above and / or problems existing in the prior art, the present application is proposed.
[0007] Therefore, the purpose of the present application is to overcome the deficiencies in the prior art and provide a preparation method of an in-situ cross-linked graphene oxide-hybrid silicon reverse osmosis membrane.
[0008] To solve the above technical problems, the present application provides the following technical scheme: a preparation method of an in-situ cross-linked graphene oxide-hybrid silicon reverse osmosis membrane, comprising,
[0009] The graphene oxide nanosheets are added to an alcohol solution, centrifuged to replace the alcohol phase, hybrid silicon precursor is added for preliminary cross-linking, and water bath stirring is performed to obtain a composite sol.
[0010] The hybrid silica precursor is added into the composite sol, mixed, and an acid catalyst and water are added to perform in-situ cross-linking reaction to obtain a polymerized sol;
[0011] The polymerized sol is coated on a ceramic support by a hot rubbing coating method, and calcination is performed to obtain an in-situ cross-linked graphene oxide-hybrid silica reverse osmosis membrane.
[0012] As a preferred scheme of the preparation method, the alcohol solution comprises one of an ethanol solution and a n-propanol solution, and the single-layer rate of the GO nanosheet is greater than 99.5%, and the radial size is 5-8 μm.
[0013] As a preferred scheme of the preparation method, the centrifugal treatment is replaced, wherein the centrifugal speed is 8000-12000 r / min, the centrifugal time is 10-20 min, and the replacement is performed 3-5 times.
[0014] As a preferred scheme of the preparation method, the silica precursor comprises 1,2-bis(triethoxysilyl)ethylene (BTESEthy) and 1,2-bis(triethoxysilyl)ethane (BTESE).
[0015] As a preferred scheme of the preparation method, the preliminary cross-linking is performed, wherein the ratio of the hybrid silica precursor to the alcohol solution is 0.1-0.2 g:15-18 g, the cross-linking reaction temperature is 70-80 °C, and the reaction time is 7-8 h.
[0016] As a preferred scheme of the preparation method, the acid catalyst comprises 37 wt% concentrated hydrochloric acid.
[0017] As a preferred scheme of the preparation method, the in-situ cross-linking reaction is performed, wherein the molar ratio of the hybrid silica precursor, water, and the acid catalyst is 1:60-90:0.1-0.2; the in-situ cross-linking reaction temperature is 40-60 °C, and the reaction time is 2-4 h.
[0018] As a preferred scheme of the preparation method, the preparation method of the ceramic support comprises,
[0019] The ceramic sheet is polished, boiled, and baked for pretreatment, a particle layer and an intermediate layer are coated to obtain the ceramic support;
[0020] The ceramic sheet is an α-Al2O3 asymmetric ceramic sheet, and the pore size is 1 μm.
[0021] The particle size of the particle layers is 1 and 0.2 microns respectively, 4-5 layers are coated, the drying temperature is 200 DEG C, the drying time is 10 minutes, and the calcination temperature is 550 DEG C and the calcination time is 20 minutes;
[0022] The coated intermediate layer is a silica-zirconia particle sol, 8-10 layers are coated, the calcination temperature is 550 DEG C and the calcination time is 20 minutes.
[0023] As a preferred scheme of the preparation method, the hot rubbing coating method is used, the rubbing coating frequency is 14-16 times, and the rubbing coating temperature is 80-150 DEG C.
[0024] The calcination temperature is 120-550 DEG C and the calcination time is 20-30 minutes.
[0025] Another object of the present application is to provide an application of the reverse osmosis membrane in reverse osmosis desalination.
[0026] The present application has the following advantages:
[0027] (1) The present application provides a preparation method of the in-situ cross-linked graphene oxide-hybrid silicon reverse osmosis membrane.
[0028] (2) The in-situ cross-linked graphene oxide-hybrid silicon reverse osmosis membrane prepared by the present application has excellent structural stability in the continuous reverse osmosis desalination application for 120 hours, and the water permeability is greater than or equal to 5.03*10 -8 mol / m 2 h Pa) and the salt rejection rate (NaCl: greater than or equal to 97.59%).
[0029] (3) The present application uses the hot rubbing coating method to prepare the in-situ cross-linked graphene oxide-hybrid silicon reverse osmosis membrane on the ceramic support. BRIEF DESCRIPTION OF DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings needed to be used in the embodiment description. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without any creative effort based on these drawings. Among them:
[0031] Figure 1 The mechanism diagram of hot rubbing coating method for the in-situ cross-linked graphene oxide / hybrid silicon reverse osmosis membrane in the embodiment 1 of the present application.
[0032] Figure 2 The SEM diagrams of surface and section of the in-situ cross-linked graphene oxide / hybrid silicon reverse osmosis membrane in the embodiment 1 of the present application.
[0033] Figure 3 The separation ion mechanism diagram of the in-situ cross-linked graphene oxide / hybrid silicon reverse osmosis membrane in the embodiment 1 of the present application.
[0034] Figure 4 The stability test diagram of the in-situ cross-linked graphene oxide / hybrid silicon reverse osmosis membrane in the embodiment 1 of the present application. DETAILED DESCRIPTION
[0035] In order to make the above-mentioned purposes, features and advantages of the present application more apparent and easy to understand, the following will make detailed description of the specific embodiments of the present application combined with the embodiment of the specification.
[0036] The reverse osmosis desalination experiment is carried out by using salt water solution. The feed liquid is pressurized to 0.5-1.8 MPa by a back pressure valve, and then continuously stirred in the reverse osmosis tank by a magnetic stirrer. The retentate is returned to the feed tank. In each test, the stable state is reached first, and then the permeate sample is collected and analyzed. The experimental data points presented in the study are the average values of three samples.
[0037] The water permeability (Lp) can be calculated by flux (J v ) divided by the effective transmembrane pressure (△P), as Eq (1):
[0038] J v = L p (△P-△π) (1)
[0039] In the formula, L p is the water permeability of the membrane, and △P (=P1-P2) and △π (=π1-π2) are the differences of the applied pressure and the osmotic pressure.
[0040] The permeation flux P RO in RO is defined on a molar basis, as Eq (2):
[0041]
[0042] wherein: v = 18 x 10 -6 m 3 / mol.
[0043] The detected salt ion rejection rate R obs Calculated from Eq (3):
[0044] R obs = (1 - C p / C f ) x 100% (3)
[0045] Wherein C f and C p are the conductivities in the raw liquid and the permeate liquid, respectively, measured by a conductivity meter.
[0046] Example 1
[0047] (1) 0.5 g of 10 mg / g aqueous phase GO (manufacturer: Hangzhou Gaosili Technology Co., Ltd., single layer rate: > 99.5%, radial size: 5-8 μm) dispersion was added to 8 g of n-propanol solvent, centrifuged at 12000 rpm for 10 min, 3 times, and replaced with alcohol phase GO for standby.
[0048] (2) The GO prepared in step (1) was added to 15.25 g of n-propanol solvent with 0.2 g of 1,2-bis(triethoxysilyl)ethane (BTESE), and stirred at 70°C for 6 h to carry out preliminary crosslinking, to obtain a composite sol.
[0049] (3) The composite sol prepared in step (2) was added to 0.8 g of 1,2-bis(triethoxysilyl)ethane (BTESE), stirred for 1 min, and then deionized water was added dropwise, followed by stirring for 1 min, and then 0.2 g of concentrated hydrochloric acid with a concentration of 37 wt% was added dropwise as a catalyst, to carry out in-situ crosslinking reaction of the silicon source precursor, water, and hydrochloric acid at a molar ratio of 1:60:0.2, at a reaction temperature of 40°C for 2 h, to obtain a 5 wt% polymerization sol.
[0050] (4) The polymerization sol prepared in step (3) was diluted to 0.5 wt%, and then coated on an α-Al2O3 ceramic sheet (manufacturer: Yuoli Electronic Ceramic Co., Ltd., pore size: 1 μm) as a separation layer (thickness about 200 nm) by a rubbing method, wherein the coating was a hot coating method, the coating frequency was 2 times, the coating temperature was 60°C, the calcination temperature was 120°C, and the calcination time was 30 min, to obtain an in-situ crosslinked graphene oxide / hybrid silicon reverse osmosis membrane.
[0051] The mechanism diagram of the hot rubbing method of the in-situ crosslinked graphene oxide / hybrid silicon reverse osmosis membrane is shown in Figure 1SEM images of the surface and cross-section of the in-situ cross-linked graphene oxide / hybrid silicon reverse osmosis membrane in Example 1 are shown in Figure 2 , indicating that the membrane surface is smooth and has no obvious cracks; by calculation, the total thickness of the separation layer and the intermediate layer of the membrane is about 780 nm; on the membrane surface, the GO nanosheets show good cross-linking with the BTESE, and no obvious nanosheet aggregation phenomenon is observed, which indicates that the GO nanosheets are uniformly distributed in the BTESE.
[0052] The separation ion mechanism diagram of the in-situ cross-linked graphene oxide / hybrid silicon reverse osmosis membrane in Example 1 is shown in Figure 3 , explaining how the BTESE is wrapped around the GO nanosheets.
[0053] The stability test diagram of the in-situ cross-linked graphene oxide / hybrid silicon reverse osmosis membrane in Example 1 is shown in Figure 4 (the test is a 120h reverse osmosis desalination performance test of the in-situ cross-linked graphene oxide / hybrid silicon reverse osmosis membrane at 25℃ on a 2000ppm NaCl solution), indicating that the in-situ cross-linking of the BTESE with the GO nanosheets hinders the swelling of the GO nanosheets in water, greatly improving the stability of the membrane.
[0054] Example 2
[0055] (1) 0.25g of 10mg / g aqueous GO (manufacturer: Hangzhou Gaosili Technology Co., Ltd., monolayer rate: >99.5%, radial size: 5-8μm) dispersion was added to 8g of n-propanol solvent, centrifuged at 12000rpm for 10min, 3 times, and replaced with alcohol-phase GO for standby.
[0056] (2) The GO prepared in step (1) was added to 0.2g of 1,2-bis(triethoxysilyl)ethane (BTESE) and 15.25g of n-propanol solvent, and stirred at 70℃ for 6h to perform preliminary cross-linking, obtaining a composite sol.
[0057] (3) The composite sol prepared in step (2) was added to 0.8g of 1,2-bis(triethoxysilyl)ethane (BTESE), stirred for 1min, then added with deionized water, continued to stir for 1min, then added with 0.2g of concentrated hydrochloric acid with a concentration of 37wt% as a catalyst, and the molar ratio of the silicon source precursor, water and hydrochloric acid was 1:60:0.2 to perform in-situ cross-linking reaction, the reaction temperature was 40℃, the reaction time was 2h, obtaining a 5wt% polymerization sol.
[0058] (4) The polymerized sol prepared in step (3) was diluted to 0.5 wt%, and then was coated on an α-Al2O3 ceramic sheet (manufacturer: Yuli Electronic Ceramics Co., Ltd., pore size: 1 μm) as a separation layer (thickness: about 200 nm) by a rubbing method, wherein the coating was a hot coating method, the number of rubbing was 2 times, the rubbing temperature was 60°C, the calcination temperature was 120°C, and the calcination time was 30 min, to obtain an in-situ cross-linked graphene oxide / hybrid silicon reverse osmosis membrane.
[0059] Example 3
[0060] (1) 0.75 g of an aqueous GO (10 mg / g, manufacturer: Hangzhou Gaosi Technology Co., Ltd., single layer rate: > 99.5%, radial size: 5-8 μm) dispersion was added to 8 g of n-propanol solvent, and was centrifuged at 12000 rpm for 10 min, 3 times, to be replaced with an alcohol phase GO for standby.
[0061] (2) The GO prepared in step (1) was added to 0.2 g of 1,2-bis(triethoxysilyl)ethane (BTESE) and 15.25 g of n-propanol solvent, and was stirred at 70°C for 6 h to perform preliminary cross-linking, to obtain a composite sol.
[0062] (3) The composite sol prepared in step (2) was added to 0.8 g of 1,2-bis(triethoxysilyl)ethane (BTESE), and was stirred for 1 min, and then deionized water was added dropwise, and was stirred for 1 min, and then 0.2 g of concentrated hydrochloric acid (37 wt%) was added dropwise as a catalyst, to perform in-situ cross-linking reaction, with a molar ratio of silicon source precursor, water, and hydrochloric acid being 1:60:0.2, at a reaction temperature of 40°C for 2 h, to obtain a 5 wt% polymerized sol.
[0063] (4) The polymerized sol prepared in step (3) was diluted to 0.5 wt%, and then was coated on an α-Al2O3 ceramic sheet (manufacturer: Yuli Electronic Ceramics Co., Ltd., pore size: 1 μm) as a separation layer (thickness: about 200 nm) by a rubbing method, wherein the coating was a hot coating method, the number of rubbing was 2 times, the rubbing temperature was 60°C, the calcination temperature was 120°C, and the calcination time was 30 min, to obtain an in-situ cross-linked graphene oxide / hybrid silicon reverse osmosis membrane.
[0064] Example 4
[0065] (1) 1 g of an aqueous GO (10 mg / g, manufacturer: Hangzhou Gaosi Technology Co., Ltd., single layer rate: > 99.5%, radial size: 5-8 μm) dispersion was added to 8 g of n-propanol solvent, and was centrifuged at 12000 rpm for 10 min, 3 times, to be replaced with an alcohol phase GO for standby.
[0066] (2) The GO prepared in step (1) was added to 0.2 g of 1,2-bis(triethoxysilyl)ethane (BTESE) in 15.25 g of n-propanol solvent, and stirred at 70°C for 6 h to perform preliminary crosslinking to obtain a composite sol.
[0067] (3) The composite sol prepared in step (2) was added to 0.8 g of 1,2-bis(triethoxysilyl)ethane (BTESE), stirred for 1 min, and then deionized water was added dropwise, followed by stirring for 1 min, and then 0.2 g of concentrated hydrochloric acid with a concentration of 37 wt% was added dropwise as a catalyst, and in-situ crosslinking reaction was performed with a molar ratio of silicon source precursor, water, and hydrochloric acid being 1:60:0.2, a reaction temperature being 40°C, and a reaction time being 2 h to obtain a 5 wt% polymerized sol.
[0068] (4) The polymerized sol prepared in step (3) was diluted to 0.5 wt%, and then was applied on an α-Al2O3 ceramic sheet (a manufacturer is Yu Li Electronic Ceramics Co., Ltd., a pore size: 1 μm) as a separation layer (a thickness is about 200 nm) by a rubbing method, wherein the rubbing was a hot coating method, the rubbing frequency was 2 times, the rubbing temperature was 60°C, the calcination temperature was 120°C, and the calcination time was 30 min to obtain an in-situ crosslinked graphene oxide / hybrid silicon reverse osmosis membrane.
[0069] Example 5
[0070] (1) 0.5 g of an aqueous phase GO (a manufacturer is Hangzhou Gaoxi Technology Co., Ltd., a single layer rate: >99.5%, a radial size: 5-8 μm) dispersion liquid was added to 8 g of n-propanol solvent, and centrifuged at 12000 rpm for 10 min for 3 times to replace it with an alcohol phase GO for standby.
[0071] (2) The GO prepared in step (1) was added to 0.2 g of 1,2-bis(triethoxysilyl)ethane (BTESE) in 15.25 g of n-propanol solvent, and stirred at 70°C for 6 h to perform preliminary crosslinking to obtain a composite sol.
[0072] (3) The composite sol prepared in step (2) was added to 0.8 g of 1,2-bis(triethoxysilyl)ethane (BTESE), stirred for 1 min, and then deionized water was added dropwise, followed by stirring for 1 min, and then 0.2 g of concentrated hydrochloric acid with a concentration of 37 wt% was added dropwise as a catalyst, and in-situ crosslinking reaction was performed with a molar ratio of silicon source precursor, water, and hydrochloric acid being 1:60:0.2, a reaction temperature being 40°C, and a reaction time being 2 h to obtain a 5 wt% polymerized sol.
[0073] (4) The polymeric sol prepared in step (3) was diluted to 0.5 wt% and then coated on an α-Al2O3 ceramic sheet (manufacturer: Yu Li Electronic Ceramics Co., Ltd., pore size: 1 μm) as a separation layer (thickness: about 200 nm) by a rubbing method, wherein the coating was a hot coating method, the number of rubbing was 2 times, the rubbing temperature was 60°C, the calcination temperature was 100°C, and the calcination time was 30 min, to obtain an in-situ cross-linked graphene oxide / hybrid silicon reverse osmosis membrane.
[0074] Comparative Example 1
[0075] The difference between this comparative example and Example 1 is that:
[0076] (3) The composite sol prepared in step (2) was added with 0.1 g of 1,2-bis(triethoxysilyl)ethane (BTESE), stirred for 1 min, and then deionized water was added dropwise, followed by stirring for 1 min, and then 0.2 g of concentrated hydrochloric acid with a concentration of 37 wt% was added dropwise as a catalyst, and the molar ratio of the silicon source precursor, water, and hydrochloric acid was 1:60:0.2 for in-situ cross-linking reaction, the reaction temperature was 40°C, and the reaction time was 2 h, to obtain a 5 wt% polymeric sol;
[0077] The other conditions were the same as in Example 1.
[0078] Comparative Example 2
[0079] The difference between this comparative example and Example 1 is that:
[0080] The composite sol prepared in step (2) was added with 2 g of 1,2-bis(triethoxysilyl)ethane (BTESE), stirred for 1 min, and then deionized water was added dropwise, followed by stirring for 1 min, and then 0.2 g of concentrated hydrochloric acid with a concentration of 37 wt% was added dropwise as a catalyst, and the molar ratio of the silicon source precursor, water, and hydrochloric acid was 1:60:0.2 for in-situ cross-linking reaction, the reaction temperature was 40°C, and the reaction time was 2 h, to obtain a 5 wt% polymeric sol;
[0081] The other conditions were the same as in Example 1.
[0082] Comparative Example 3
[0083] The specific operations of steps (1), (3), and (4) were the same as in Example 1, and the preliminary cross-linking process of step (2) was omitted, and the specific steps were as follows:
[0084] (1) 0.5 g of an aqueous GO dispersion with a concentration of 10 mg / g was added to 8 g of n-propanol solvent, centrifuged at 12000 rpm for 10 min, 3 times, and replaced with an alcohol phase GO for standby.
[0085] (2) The alcohol phase GO prepared in step (1) is added with 0.8 g of 1,2-bis(triethoxysilyl)ethane (BTESE) and stirred for 1 min, then deionized water is added dropwise, and after stirring for 1 min, 0.2 g of concentrated hydrochloric acid with a concentration of 37 wt% is added dropwise as a catalyst, and in-situ crosslinking reaction is performed with a molar ratio of silicon source precursor, water and hydrochloric acid of 1:60:0.2, a reaction temperature of 40°C and a reaction time of 2 h, to obtain a 5 wt% polymeric sol.
[0086] (3) The polymeric sol prepared in step (2) is diluted to 0.5 wt%, and then is applied on an α-Al2O3 ceramic sheet as a separation layer (thickness of about 200 nm) by a rubbing method, wherein the rubbing is a hot coating method, the rubbing frequency is 2 times, the rubbing temperature is 60°C, the calcination temperature is 120°C, and the calcination time is 30 min, to obtain a graphene oxide / hybrid silicon reverse osmosis membrane.
[0087] The experimental results of the reverse osmosis desalination performance test (20 h) of the above examples and comparative examples on a 2000 ppm NaCl solution at 25°C are shown in Table 1.
[0088] Table 1
[0089]
[0090]
[0091] The reason for the poor effect of Comparative Example 1 is that the amount of BTESE added is too small to completely wrap the GO nanosheet, so that the ions cannot be effectively intercepted.
[0092] The reason for the poor effect of Comparative Example 2 is that the amount of BTESE added is too large, so that the hybrid silicon network is entangled and connected, affecting the water permeation and the effective inhibition of ion entry.
[0093] The reason for the poor effect of Comparative Example 3 is that no preliminary crosslinking is performed, so that the GO nanosheet is not preliminarily arranged in order, and the GO nanosheet is stacked, thereby affecting the water permeation.
[0094] The GO is preliminarily crosslinked with a small amount of organic silicon precursor to arrange the GO nanosheet in order, and then the polymeric sol is prepared by in-situ crosslinking of the hybrid silicon catalyzed by acid. The hybrid silicon network is wrapped around the two layers of GO nanosheet to form a gate, effectively inhibiting the entry of ions and improving the separation performance. The hybrid silicon forms a certain support in the two layers of GO nanosheet to support the GO nanosheet layer, thereby improving the stability of the membrane. A small amount of GO nanosheet fragments are embedded on the support to provide a large number of oxygen-containing functional groups, thereby further improving the hydrophilicity of the membrane and the water flux of the membrane.
[0095] The GO / silicone composite matrix reverse osmosis membrane was prepared on the ceramic support by hot rubbing coating method. The sol was uniformly dispersed on the support, the solvent was quickly volatilized, and the membrane layer with uniform thickness and smooth surface was formed, and the stable separation layer was formed after post-processing.
[0096] It should be noted that the above examples are only used to illustrate the technical solutions of the present application and are not limiting. Although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or equivalently replaced without departing from the spirit and scope of the technical solutions of the present application, which should be covered in the scope of the present application.
Claims
1. A method for preparing an in-situ crosslinked graphene oxide-hybrid silicon reverse osmosis membrane, characterized in that: include, Graphene oxide (GO) nanosheets were added to an alcohol solution, centrifuged to replace the alcohol phase, and a hybrid silicon precursor was added for initial cross-linking. The mixture was then stirred in a water bath to obtain a composite sol. A hybrid silicon precursor was added to the composite sol and mixed. An acidic catalyst and water were then added to carry out an in-situ crosslinking reaction to obtain a polymer sol. The polymerized sol was coated onto a ceramic support by a hot-brush coating method, and then calcined to obtain an in-situ cross-linked graphene oxide-silicon hybrid reverse osmosis membrane.
2. The preparation method according to claim 1, characterized in that: The alcohol solution includes one of ethanol solution and n-propanol solution, and the GO nanosheets have a monolayer ratio of greater than 99.5% and a radial size of 5-8 μm.
3. The preparation method according to claim 1 or 2, characterized in that: The centrifugation process involves centrifugation at a speed of 8000–12000 r / min for 10–20 min, followed by 3–5 replacements.
4. The preparation method according to claim 1 or 2, characterized in that: The silicon precursors include 1,2-bis(triethoxysilyl)ethylene (BTESEthy) and 1,2-bis(triethoxysilyl)ethane (BTESE).
5. The preparation method according to claim 1 or 2, characterized in that: The preliminary crosslinking process involves a hybrid silicon precursor to alcohol solution ratio of 0.1–0.2 g: 15–18 g, a crosslinking reaction temperature of 70–80 °C, and a reaction time of 7–8 h.
6. The preparation method according to claim 1 or 2, characterized in that: The acidic catalyst comprises 37 wt% concentrated hydrochloric acid.
7. The preparation method according to claim 1 or 6, characterized in that: In the in-situ crosslinking reaction, the molar ratio of the hybrid silicon precursor, water, and acidic catalyst is 1:60-90:0.1-0.2; the in-situ crosslinking reaction temperature is 40-60℃, and the reaction time is 2-4h.
8. The preparation method according to claim 1, characterized in that: The method for preparing the ceramic support includes: The ceramic sheet is pretreated by grinding, boiling and baking, and then coated with a particle layer and an intermediate layer to obtain a ceramic support. The ceramic sheet is an α-Al2O3 asymmetric ceramic sheet with a pore size of 1 μm. The particle sizes of the particle layers are 1μm and 0.2μm, respectively. Four to five layers are coated. The drying temperature is 200℃ and the drying time is 10min. The calcination temperature is 550℃ and the calcination time is 20min. The intermediate coating layer is a silica-zirconia particle sol, with 8-10 layers applied. The calcination temperature is 550℃ and the calcination time is 20 minutes.
9. The preparation method according to claim 1, characterized in that: The hot rubbing coating method involves 14 to 16 rubbing cycles at a temperature of 80 to 150°C. The calcination process yields an in-situ cross-linked graphene oxide-hybrid silicon reverse osmosis membrane, wherein the calcination temperature is 120–550°C and the calcination time is 20–30 min.
10. The application of the reverse osmosis membrane prepared by any one of claims 1 to 9 in reverse osmosis desalination.